Sosialisasi Keselamatan Berlalu Lintas untuk Mengurangi Angka Kejadian Kecelakaan Bagi Pelajar di SMAN 1 Selong Kabupaten Lombok Timur - Achmad Fajar Narotama Sarjan; Fera Fitri Salsabila; Aryani Rofaida (Pascasarjana Universitas Mataram, 2022)
Abstract: Currently the safety level in the province of NTB is above the national average safety rate, this is indicated by the accident fatality ratio per 100,000 which is 11.07 while the national average safety rate is 10.47, this figure must continue to reduce the risk factors for accidents. Based on NTB, the 2017 figures show that in 2016 the largest number of accident perpetrators were at the Junior High School (SMP) level, namely 38%. Seeing this data, it is necessary to increase public awareness of the importance of safety and how to maintain safety while driving. One of the efforts to increase public awareness of safety can be done by socializing driving safety. Safety socialization is carried out to provide understanding, awareness, and knowledge about driving procedures and how to maintain road safety.